The features of formation of the surface gradient layers in zirconium - Kirichenko, V.G.; Yampolskyi, O.O. (Вопросы атомной науки и техники, 2017)
It was found that increasing the surface concentration of iron atoms in zirconium alloys in the surface layer thickness up to 0.3 μm results to the formation of gradient structures. This process can help to optimize the physical and mechanical characteristics of the alloys due to intermetallic compounds enriched surface layer. Виявлено, що збільшення поверхневої концентрації атомів заліза в сплавах цирконію в поверхневому шарі товщиною до 0,3 мкм призводить до формування градієнтних структур. Цей процес, в свою чергу, може сприяти оптимізації фізико-механічних характеристик сплавів за рахунок збагаченого інтерметаліда поверхневого шару. Установлено, что увеличение поверхностной концентрации атомов железа в сплавах циркония в поверхностном слое толщиной до 0,3 мкм приводит к формированию градиентных структур. Этот процесс, в свою очередь, может способствовать оптимизации физико-механических характеристик сплавов в результате обогащенного интерметаллида поверхностного слоя.